Pemetaan Jaringan Pengetahuan: Analisis Jaringan Sastra Sistematis Permainan Banyumasan dan Berpikir Kritis Anak - Murni Murni; Eneng Sri Susilawati; Erie Siti Syarah (SENTRI: Jurnal Riset Ilmiah, 2026)
Critical thinking is increasingly recognized as a core competency of the 21st century that must be cultivated from the early stages of education. However, in early childhood education practices, the development of critical thinking still tends to focus on formal approaches and modern or digital games, while the potential of traditional games rich in cultural context and cognitive challenges has not been systematically studied. Traditional cultural practices are often positioned merely as recreational activities, rather than as pedagogical media for developing children's higher-order thinking skills. Therefore, this study aims to examine how traditional Banyumasan games, particularly Lowok and Lithongan, contribute to fostering children's critical thinking skills. Through Systematic Literature Network Analysis (SLNA), this study reviewed and mapped 163 scientific articles indexed by Scopus and Web of Science published between 2010 and 2024. Bibliometric and network analyses were conducted using VOS viewer to identify keyword relationships, co-citation patterns, bibliographic coupling, and collaboration networks between authors, institutions, and countries. The research findings reveal four main clusters: critical thinking and problem-solving in early childhood education, culture-based pedagogy through traditional games, collaborative learning and social interaction, and the integration of 21st-century skills in a game-based approach. The mapping results also indicate that neuroscientific perspectives examining the cognitive and neural mechanisms underlying traditional game-based learning remain underexplored, highlighting a significant research gap in this field. Although this field is rapidly developing, publications are still dominated by American and European sources, with contributions from Southeast Asia limited. This research contributes to the development of educational science by demonstrating how culture-based pedagogical practices can strengthen children's critical thinking skills while opening up cross-cultural and longitudinal research directions.